2022
DOI: 10.1097/ijg.0000000000002063
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Prolene Gonioscopy Assisted Transluminal Trabeculotomy in Primary Open Angle Glaucoma and Pseudoexfoliation Glaucoma: A Comparative Study

Abstract: Précis: Gonioscopy-assisted transluminal trabeculotomy (GATT) provides greater intraocular pressure (IOP) reduction in pseudoexfoliative glaucoma (PXG) than in primary open angle glaucoma (POAG) in the first year of surgery; however, the difference between groups equalizes in the long term. Purpose: To compare outcomes of GATT in eyes with POAG and PXG. Methods: Single-center, retrospective, comparative case-series. A total of 202 eyes (91 eyes of POAG; 111 eyes of PXG) were included. GATT was performed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The results of this retrospective study demonstrate good surgical success rates as well as good IOP and medication reduction across a wide range of glaucomas, in a diverse population, in combination with lens extraction or as a standalone procedure. These results are in line with current literature on GATT 23 , which has been accumulating since the initial report by Grover et al 1 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this retrospective study demonstrate good surgical success rates as well as good IOP and medication reduction across a wide range of glaucomas, in a diverse population, in combination with lens extraction or as a standalone procedure. These results are in line with current literature on GATT 23 , which has been accumulating since the initial report by Grover et al 1 .…”
Section: Discussionsupporting
confidence: 92%
“…They reported a decrease of 8.8 mmHg (34.4%) and 12.8 (44.6%) in the POAG and PXG groups, respectively. Cumulative success at 1 year in POAG was 86.8% 23 , similar to our results in the combined and solo groups.…”
Section: Discussionsupporting
confidence: 89%
“…This researcher notes that in most cases of previous surgery, an extended opening of the canal was possible, which is similar to our observation. Cubuk et al [32] found that the results of GATT as the second procedure were better in PEXG than in POAG patients, which is similar to the results in naive patients [7].…”
Section: Discussionmentioning
confidence: 63%
“…The GATT technique introduced by Grover et al [6] consists of peeling the interior wall of the Schlemm's canal and perfectly matches the pathogenesis of IOP increase in glaucoma, which is related to the enhanced outflow resistance at this site. Since its introduction, the application of the GATT technique has been described in different types of glaucoma [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Patients with pseudoexfoliative glaucoma (PEXG) seem to have more favorable success rates (79%) compared to primary OAG (POAG) (73%); however, the difference was not statistically significant at the end of the 3rd year. 10 Future glaucoma research focuses on restoring the functionality of the TM and also the distal outflow system. Patients who have undergone GATT or have already dysfunctional distal outflow may just, therefore, become ineligible for these therapeutic options.…”
Section: R Ationale Behind Gatt S Urgery...mentioning
confidence: 99%